Using RAPD-PCR to Determine the Genetic Stability of Dianthus Chinesis in Vitro Treated with the Chemical Mutagenic Ethyl Methyl Sulfonate EMS - Jayed, Ghufran Adnan; Alsugmiany, Rafea Zaidan Mukhlif; Ghanim, Nadhim Salim (Journal La Lifesci, 2022)
This study was conducted in the Molecular Biology Lab. and the Central Lab. at the University of Tikrit on 1/29/2023 for the purpose of determining the genetic stability of the Dianthus chinesis after cultivating it in vitro using 3 RAPD primers, which are OPA-02, OPD-10, OPD- 18, As 9 samples were used in the study, the first is a field sample of this plant that was not treated with EMS (was considered as a control sample) and the remaining samples (4 callus samples and 4 tissue branches samples) were treated with concentrations of (0.0, 0.2, 0.4, 0.6)% of EMS, after a month, DNA was extracted, RAPD reactions were performed for the primers used ,as it was shown through the results that there was a genetic variation in the genetic material of the Dianthus chinesis in the recognition sites of the used primers, as it was not only affected by EMS, but by its cultivation in vitro.